Macrophages and the immune microenvironment in OPMDs: a systematic review of the literature - Sutera, Samuele; Furchì, Olga Anna; Pentenero, Monica (Frontiers in Oral Health, 2025)
BackgroundIn the presence of cancers, Tumor Associated Macrophages have a well-established role, but the literature provides limited evidence regarding their involvement in the onset and malignant transformation of Oral Potentially Malignant Disorders (OPMDs).ObjectivesThe present systematic review aimed to collect evidence on the presence and characterization of macrophages in the microenvironment of OPMDs.Data sourcesPubMed, Scopus, EMBASE, Web of Science.Study eligibility criteriaEx vivo or in silico human studies reporting original quantitative data on macrophage infiltration in OPMDs or Oral Epithelial Dysplasia (OED), published from 1990 onward.ResultsThirty-seven studies were included for qualitative analysis. Investigated OPMDs included: oral leukoplakia, oral lichen planus, oral lichenoid lesions, proliferative leukoplakia, oral submucous fibrosis, actinic cheilitis, chronic graft vs. host disease.DiscussionEven though the heterogeneity of data from the included studies prevents a meta-analysis, the reported results are quite consistent in supporting an increasing macrophage infiltration from normal mucosa to OPMDs, OED, and Oral Squamous Cell Carcinoma (OSCC). An M1 pro-inflammatory polarization is prevalent in OPMDs, with a shift toward an M2 pro-tumorigenic polarization in moderate-severe OED and OSCC. Several novel markers including STAT1, IDO, PD-L1, APOE, ITGB2 appear to be able to identify macrophage clusters involved in pro-inflammatory or pro-tumorigenic pathways.ConclusionsEvidence from the present review supports an active role of macrophages in regulating immune suppression, oncogenesis, and tumor progression in OPMDs and during the transition to OSCC. Future research should focus not merely on cell quantification and general M1/M2 polarization but rather on the expression of specific markers potentially linked to immunomodulatory pathways involved in oncogenesis.